Determinants of the expected real long-term interest rates in the G7-countries - Jörg W. Krämer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
The paper investigates which factors determine the expected real long-term interest rates of the G7-countries as a whole within a single equation error correction model. Inflationary expectations are generated using the low frequency component of inflation provided by the Hodrick-Prescott filter. A comparision of the calculated expected inflation rates with those resulting from index-linked and conventional UK bonds suggests this approach to be appropriate. Expected real long-term interest rates turn out to be influenced positively by real short-term interest rates, capacity utilization and structural public borrowing.
Keywords: C22; E43; 330; Realzins; Zins; Inflationserwartung; Schätzung; G-7-Staaten